SOA patterns with Biztalk Server 2013 and Microsoft Azure : learn how to create and implement SOA strategies on the Microsoft technology stack using BizTalk server 2013 and Azure Integration platforms /: learn how to create and implement SOA strategies on the Microsoft technology stack using BizTalk server 2013 and Azure Integration platforms. (2015) - Seroter, Richard
No abstract available